Parameter determination for a computer simulation model of a diver and a springboard - Fred Yeadon; Pui W. Kong; Mark King (2006)
This study used kinematic data on springboard diving performances to estimate visco-elastic parameters of a planar model of a springboard and diver with wobbling masses in the trunk, thigh and calf segments and spring-dampers acting at the heel, ball and toe of the foot segment. A subject-specific angle-driven eightsegment model was used with an optimisation algorithm to determine visco-elastic parameter values by matching simulations to four diving performances. Using the parameters determined from the matching of a single dive in a simulation of another dive resulted in up to 31% difference between simulation and performance, indicating the danger of using too small a set of kinematic data. However using four dives in a combined matching process to obtain a common set of parameters resulted in a mean difference of 8.6%. Since these four dives included very different rotational requirements, it is anticipated that the combined parameter set can be used with other dives from these two groups.